Representation of American Women Spirit of 21st Century Through the Character of Agent Peggy Carter From Television Series Marvel Agent’s: Carter (ABC, 2015 - 2016) - Sulistio, Anindhitya Rahiswari (Universitas Sebelas Maret, 2023)
This research is written to analyze the representation of Agent Peggy Carter in television series Marvel Agent’s: Carter (ABC, 2015 – 2016). Agent Peggy Carter is an agent turns into secretary who works in secret division of Strategic Scientific Reserve. Agent Peggy Carter tried to fight against sexism from her male counterparts in the workplace. The television series was planned to be produced into three seasons. However, due to the low rating in the second season, the production cancelled the plan to make the third season. The series highlight Agent Carter’s struggle against sexism. The research used female action hero theory to analyze about Agent Carter representation as female action hero and Semiotic film theory. The result shows that Agent Carter representing female action hero and how Agent Carter representing the spirit of American women in twenty first century.